VD_FINDINFO Jug / 2017 / 182 vom 22. Dezember 2016 - VD Tribunal cantonal (2016)
DIFFAMATION, CONSTATATION DES FAITS, PREUVE LIBÉRATOIRE | 106 CP, 173 ch. 1 CP, 34 CP, 42 al. 1 CP, 42 al. 4 CP, 44 al. 1 CP, 47 CP